Responses of iliac conduit artery and hindlimb resistance vessels to luminal hyperfructosemia in the anaesthetized pig. (7th October 2013) - Ruane‐O'Hora, T.; Edge, D.; Shortt, C. M.; Markos, F.; Noble, M. I. M.
Abstract Aims High fructose levels are found in diabetes mellitus, associated with high corn syrup diets, and have been claimed to cause hypertension. As the direct effects on conduit and resistance arteries have not been previously reported, we measured these in vivo in the anaesthetized pig with instrumented iliac arteries. Methods Experiments were performed on the iliac artery preparation in the anaesthetized pig: blood flow, diameter and pressure were measured in the iliac. Results The change in diameter of an occluded iliac artery segment filled with hyperfructosemic (15 μm) blood was 89.5 ± 22.1 μm (mean ± SE), contrasted with 7.7 ± 13.06 μm control (P = 0.005, paired t‐test, n = 6). There was no significant difference when compared with blood containing both hyperfructosemic blood and the nitric oxide synthesis inhibitor, N(G)‐nitro‐l‐arginine methyl ester (250 μg mL−1). Step changes in pressure and flow were achieved by progressive arterial stenosis during control saline and 15 μm min−1 fructose downstream intra‐arterial infusions. Linear regression of the step changes in blood pressure versus the instantaneous step changes in blood flow showed a statistically significant decrease in slope of the conductance (P < 0.001, analysis of covariance), indicating an increase in instantaneous peripheral vascular resistance. Peripheral autoregulation and conduit artery shear‐stress‐mediated dilatation were not significantly altered. Conclusion An elevated level of fructose caused dilatation of a conduit artery but constriction of resistance vessels. The latter effect could account, if maintained long‐term, for the hypertension claimed to be due to hyperfuctosemia.